2005
DOI: 10.1097/01.brs.0000159096.11248.6d
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus Pulposus Cells Upregulate PI3K/Akt and MEK/ERK Signaling Pathways Under Hypoxic Conditions and Resist Apoptosis Induced by Serum Withdrawal

Abstract: It is concluded that under hypoxic conditions, rat nucleus pulposus cells are adapted for survival by regulation of expression of critical genes, downregulation of apoptosis through activation of the PI3K/Akt and MAPK survival pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 29 publications
7
106
0
1
Order By: Relevance
“…However, only limited studies have appeared until now reporting the activation and/or the function of these pathways in IVD cells or tissues [34][35][36]. Accordingly, we have studied the activation of the MEK/ ERK and the PI 3-K/Akt pathways in bovine IVD cells in response to PDGF, bFGF and IGF-I.…”
Section: Discussionmentioning
confidence: 99%
“…However, only limited studies have appeared until now reporting the activation and/or the function of these pathways in IVD cells or tissues [34][35][36]. Accordingly, we have studied the activation of the MEK/ ERK and the PI 3-K/Akt pathways in bovine IVD cells in response to PDGF, bFGF and IGF-I.…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrated that galectin 3 has a prosurvival role in the intervertebral disc (7). Moreover, Risbud and colleagues showed that hypoxia confers protection against apoptosis via the PI3K/Akt and MAPK pathways in nucleus pulposus cells (8). More recently, as discussed by Gogate et al (9), hypoxia was shown to regulate expression of ␤-1,3-glucuronyltransferase 1 nucleus, a key enzyme in glycosaminoglycan synthesis in nucleus pulposus cells.…”
Section: To the Editormentioning
confidence: 97%
“…Nucleus pulposus cells generate energy through anaerobic glycolysis rather than through oxidative phosphorylation (4); thus, it is not surprising that a hypoxia-regulated pathway plays an important role in nucleus pulposus cell survival. In fact, a number of recent studies also demonstrated that hypoxia regulates nucleus pulposus survival via other signaling molecules, including vascular endothelial growth factor (VEGF) (5,6), galectin 3 (7), phosphatidylinositol 3-kinase [PI3K]/Akt, and MAPK (8), in a hypoxia-inducible factor (HIF)-independent manner. Indeed, a study by Fujita and colleagues has shown that VEGF and its receptors are expressed by nucleus cells in hypoxia and that this protein promotes nucleus pulposus survival (5).…”
Section: To the Editormentioning
confidence: 99%
“…In addition, an important consideration is the harsh microenvironment within the degenerated intervertebral disc, which is characterised by reduced oxygen (Grunhagen et al, 2006) and reduced glucose concentration, (Bibby et al, 2005) creating a challenge in maintaining viable cellular populations (Antoniou et al, 1996). For chondrocytes, tissue specific oxygen gradients have been shown to play an important role in maintaining tissue phenotype through the hypoxia inducible factor (HIF) family of nuclear regulatory elements (Malda et al, 2003) in a similar manner to TGF-β supplementation through MEK/ERK and PI3k/Akt pathways (Pratsinis et al, 2012;Risbud et al, 2005).…”
Section: Introductionmentioning
confidence: 99%